THE IMPACT OF CHRONIC PESTICIDE ON INCIDENCE OF GASTRIC CANCER: SYSTEMATIC REVIEW AND META-ANALYSIS - Khoiruddin, Mukhammad Arif Hadi; Tartila, Jasmine; Utami, Wiwien Sugih; Kusuma, Irawan Fajar (HEARTY, 2024)
Indonesia as an agricultural country relies heavily on its corps as the main sector of nation’s development. On daily basis, many farmers use pesticide to increase corps productivity. However, pesticides were known to induce malignancy, one of them being gastric cancer; the fourth most mortal cancer in the world, with less than 12 month life expectancy on advanced stage, thereby making it a global health problem. This research used systematic review and meta-analysis methods to examine pesticide exposure variables on gastric cancer cases. Three journals were found, and meta-analysis results showed that there was a significant increase in the risk of gastric cancer in respondents who experienced pesticide exposure, especially with prolonged exposure with an odds ratio of 1.47 (more than two years). However, this review cannot explain the toxicity dose of pesticides and the nutritional status of respondents which can increase the incidence of gastric cancer due to the lack of research on related variables.